PRODUCTION DESIGN IN THE CREATION OF THE SHORT FILM BEHIND THE DOOR : (A Qualitative Approach to Cinematography and Visual Storytelling) - Ken Norton Hutasoit; Tuty Mutiah; Ali Imron Hamid (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2026)
This study examines the process of making a short film entitled “Behind the Door”, which has a psychological and mystery theme. Audio-visual works with optimized artistic and technical work are the main objectives of this design. Pre-production, production, and post-production are all part of the design process, which focuses on script creation, storyboarding, location selection, and lighting and sound arrangements to support the mood of the story. To ensure the quality of production in accordance with cinematographic standards, this design uses a qualitative approach by conducting literature research, observation, and interviews with film practitioners. It is hoped that this design will become a model for making short films that can convey story messages and provide a deep experience to the audience.